Dispersi Polutan Karbon Monoksida di Sekitar Pintu Tol Baranangsiang Bogor (Carbon monoxide Dispersion in the Vicinity of Baranangsiang Toll Gateway in Bogor) - Yudith Vega Paramitadevi (IPB University, 2014)
Over the past decade, emission from carbon monoxide (CO) has risen due to the increase of vehicles per year. Bogor as a weekend tourist tour town has a heavy burden in the terms of the volume of motor vehicles. The object of this study is Baranangsiang Bogor toll gateway, where queue of motor vehicles is often the case, and allegedly produces many pollutants CO. This study was conductes to simulate the CO concentration by the method of Finite Length Line Source (FLLS) aroung Baranangsiang Bogor toll gateway and recapitulate types of diseases associated with CO impacts on communities around the toll is in line with the pattern of increase in the volume of vehicles at 6% per years. Based on the result of measurements and simulations that were conducted on four sampling points within 20 m and 190 m from the sources pollutions on 26th August to 1st September 2014, the concentration of CO is still within the range of quality standards in accordance with Regulation No. 41 of 1999 which is 634-9189 µg/Nm3. Dispesion of pollutants CO dominantly heading Eastwards with the wind speed measurements 1.5-5.2 m/s and atmospheric stability class B. Kampung Sawah RT 02 RW 07is exposed to higher CO. Recapitulation of medical records showed that CO intoxication suspected cases of the disease are more common in Kampung Sawah housing than IPB Baranangsiang 4 Settlement.Keywords : Baranangsiang Toll Gate, Carbon Monoxide, CO Intoxication, Dispersion CO